THE INFLUENCE OF READING HABIT AND GRAMMAR KNOWLEDGE ON THE STUDENTS’ CAPABILITY OF WRITING NARRATIVE TEXTS - Pao, Benisius (LingTera, 2016)
This research aims to investigate the influence of (1) reading habit on the students’ capability of writing narrative texts, (2) knowledge of grammar on the students’ capability of writing narrative texts, and (3) reading habit and knowledge of grammar on the students’ capability of writing narrative texts. This research is an expost facto study, involving two independent variables and one dependent variable. The population comprised the third semester students of English Study Program in the Language and Arts Faculty of Flores Universities in the academic year of 2013/2014, consisting of 55 students. The data were collected through a reading habit questionnaire, test of grammar knowledge and writing narrative test. A prerequisite analysis was conducted before the analysis of multiple linear regressions. Based on regresión analysis, it can be concluded that reading habit influences the students’ capability of writing narrative texts (β = 0.745, p 0.05), knowledge of grammar influences the students’ capability of writing narrative texts (β = 1.304, p = 0.05) and reading habit and knowledge of grammar influence the students’ capability of writing narrative texts (R²=0574, F-count=35.073, p ˂ 0.05).